FUNGSI AFEKTIF KELUARGA BERHUBUNGAN DENGAN TINGKAT STRES PADA WANITA MENIKAH USIA DINI DI PEDUKUHAN JARANAN DESA BANGUNTAPAN KABUPATEN BANTUL YOGYAKARTA - Yuli Septiningsih; Dian Nur Adkhana Sari; Endar Timiyatun (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Backround: Family afective function is very importand to be fulfilled in a family to minimize the stress on family members, especially in woman family members who married early age. Objective: the aim of this research is to determine the relationship between family function with stress level in married couples early age in Pedukuhan Jaranan Banguntapan Bantul Yogyakarta Method: In this study using cross sectional method that is approach at one time coinciding with chi square corelation test, sampling technique use total sampling with the amount of respondents 37 woman early married. Results: There is a relationship of family afective function with stres level in woman early married age with result p value 0,050. Conclusion: there is a relationship of family afective function with stress level in woman married of early age in Pedukuhan Jaranan Banguntapan Bantul Yogyakarta.